Clinical significance of the immunoglobulin G heavy‐chain repertoire in peripheral blood mononuclear cells of adult T‐cell leukaemia–lymphoma patients receiving mogamulizumab. (10th October 2021) - Nosaka, Kisato; Kusumoto, Shigeru; Nakano, Nobuaki; Choi, Ilseung; Yoshimitsu, Makoto; Imaizumi, Yoshitaka; Hidaka, Michihiro; Sasaki, Hidenori; Makiyama, Junya; Ohtsuka, Eiichi; Jo, Tatsuro; Ogata, Masao; et al.
Summary: 'Monitoring of immune responses following mogamulizumab‐containing treatment in patients with adult T‐cell leukaemia–lymphoma (ATL)' (MIMOGA) is a multicentre prospective clinical study (UMIN000008696). In the MIMOGA study, we found that a lower percentage of CD2 − CD19 + B cells in peripheral blood mononuclear cells (PBMC) was a significant unfavourable prognostic factor for overall survival (OS). Accordingly, we then analysed the immunoglobulin G (IgG) heavy‐chain repertoire in PBMC by high‐throughput sequencing. Of the 101 patients enrolled in the MIMOGA study, for 81 a sufficient amount of PBMC RNA was available for repertoire sequencing analysis. Peripheral IgG B cells in patients with ATL had a restricted repertoire relative to those in healthy individuals. There was a significant positive correlation between the Shannon–Weaver diversity index (SWDI) for the IgG repertoire and proportions of B cells in the PBMC of the patients. Multivariate analysis identified two variables significantly affecting OS: a higher serum soluble interleukin‐2 receptor level, and a lower SWDI for the IgG repertoire [hazard ratio, 2·124; 95% confidence interval, 1·114–4·049; n  = 44]. The present study documents the importance of humoral immune responses in patients receiving mogamulizumab‐containing treatment. Further investigation of strategies to enhance humoral immune responses in patients with ATL is warranted.